Experiential Learning in Metrology and Quality Engineering Course - Vijayakumar, N.; Gaitonde, V. N.; Lakkundi, A. R.; Madhusudhana, H. K.; Jangali Satish, G. (Journal of Engineering Education Transformations, 2015)
Technical education programs have embraced experiential learning as a true learning methodology for students to obtain occupational skills valued by employers. Programs have integrated classroom instruction with laboratory experiences to provide students a significant opportunity to learn. A fundamental component in professional education is the link between theory and practice. However, many students in professional education programs experience a lack of coherence between theory and practice, which is often described as the theory practice gap. This work is apart of "Bridging the Gap" in metrology and quality engineering course, designed for the undergraduate students of VI Semester Industrial and Production Engineering of BVBCET, Hubli, an autonomous institute. Two problem statements were given to the students; one was on the process capability analysis of machines and another on the construction of control chart for variables, which they have to solve after conducting the experiments in machine shop in batches. The students had to chalk out the necessary information to conduct the experiment like profile, sample size, subgroup size and finally analyze the experimental data to decide whether machine is capable to meet the specifications of part and detect the presence of assignable or un assignable causes of variation using process capability analysis and control chart respectively. After the completion of this exercise, the students could realize the importance of process capability analysis and control charts in the manufacturing industries. This activity was step forward in bridging the gap between theory and lab through experiential learning. The performance indicators (PIs) of the ABET program outcome ’3b’ were underlying the motivators while designing the present experiential learning activity.